2020
DOI: 10.1186/s12936-020-03318-1
|View full text |Cite
|
Sign up to set email alerts
|

An observational analysis of the impact of indoor residual spraying in Northern, Upper East, and Upper West Regions of Ghana: 2014 through 2017

Abstract: Background Ghana has been implementing the indoor residual spraying (IRS) of insecticides since 2006, focusing operations in the north. Insecticide resistance concerns prompted a switch from pyrethroids to organophosphates, beginning gradually in 2011 and switching fully to the micro-encapsulated formulation of pirimiphosmethyl (PM CS), Actellic ® 300CS, a third-generation indoor residual spraying (3GIRS) product, by 2014. Entomological surveillance studies have shown IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 12 publications
3
15
0
Order By: Relevance
“…For example, compared to no IRS, we found that women living in households sprayed against mosquitoes or treated with indoor residual insecticide recorded a 6.8% absolute reduction in self-reported malaria prevalence. This was also consistent with findings from a district-level observational study in the northern region of Ghana in which there was a 39%, 26% and 58% relative reduction in confirmed malaria cases in 2015, 2016 and 2017 respectively among IRS campaigned districts compared to non-IRS campaigned districts [ 24 ]. In another study in the Bunkpurugu-yunyoo district in northern region of Ghana, there was an estimated 5% marginal decline in asexual parasitaemia prevalence among children from 52% in November 2010 to 48% in October 2012 during a high transmission season after application of alpha-cypermethrin IRS between the two periods.…”
Section: Discussionsupporting
confidence: 90%
“…For example, compared to no IRS, we found that women living in households sprayed against mosquitoes or treated with indoor residual insecticide recorded a 6.8% absolute reduction in self-reported malaria prevalence. This was also consistent with findings from a district-level observational study in the northern region of Ghana in which there was a 39%, 26% and 58% relative reduction in confirmed malaria cases in 2015, 2016 and 2017 respectively among IRS campaigned districts compared to non-IRS campaigned districts [ 24 ]. In another study in the Bunkpurugu-yunyoo district in northern region of Ghana, there was an estimated 5% marginal decline in asexual parasitaemia prevalence among children from 52% in November 2010 to 48% in October 2012 during a high transmission season after application of alpha-cypermethrin IRS between the two periods.…”
Section: Discussionsupporting
confidence: 90%
“…4 It is of note that none of the trials that evaluated the impact of adding IRS with a “non-pyrethroid-like” insecticide assessed outcomes beyond two years. More recently, observational studies evaluating the effectiveness of pirimiphos-methyl (Actellic 300CS®) in “real world” settings have documented impressive impacts of IRS in Mali 8,9 , Ghana 10 , Zambia 11 , Kenya 12 , and Uganda. 7 This analysis contributes to observational data on the impacts of sustained IRS beyond 6 years, in the context of the COVID-19 pandemic and a switch to products containing the active ingredient clothianidin.…”
Section: Discussionmentioning
confidence: 99%
“…Malaria transmission is spatio-temporally heterogenous in Ghana with intensities highly driven along different ecological zones [ 30 , 31 ]. Recently, malaria prevalence in under 5 years was estimated to be about 40% [ 32 ]. Vector control with IRS and LLINs has been a key strategy for malaria control, where an estimated LLIN usage of 73% was previously recorded and reduction of malaria burden has been attributed to the effectiveness of these tools [ 32 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, malaria prevalence in under 5 years was estimated to be about 40% [ 32 ]. Vector control with IRS and LLINs has been a key strategy for malaria control, where an estimated LLIN usage of 73% was previously recorded and reduction of malaria burden has been attributed to the effectiveness of these tools [ 32 34 ]. Anopheles coluzzii , An.…”
Section: Introductionmentioning
confidence: 99%